The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1540-5842.2009.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

The Essence of Islamist Resistance: A Different View of Iran, Hezbollah and Hamas

Abstract: The Iranian revolution -the political realization of the "Great Refusal" of Western modernization -was a direct consequence a half century later of the forced secularization of the Ottoman Caliphate by Kemal Ataturk. With the superstructure of the Muslim ummah dismantled and replaced by the Turkish nation state, insurgent religious movements, from the (Sunni) Muslim Brotherhood in Egypt to the Shiite imams of Qum and Najaf, moved into the vacuum to reclaim Islam from the shadow of Western dominance.Now, histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[as] a messianic saviour to implement a transfiguration of the world' in ways not so very different from claims of legitimacy issued by many non-state armed actors from the Middle East. 44 Numerous studies have also indicated a positive relationship between the articulation of a strong Christian faith and recruitment patterns within all branches of the United States military. burdette et al, for instance, find this to be true of a large cross-section of male college students; both for those they classify as 'highly religious evangelical' and 'moderately religious nonevangelical', with the 'nonreligious consistently exhibit[ing] lower odds of enlistment' overall.…”
Section: Us Versus Themmentioning
confidence: 99%
“…[as] a messianic saviour to implement a transfiguration of the world' in ways not so very different from claims of legitimacy issued by many non-state armed actors from the Middle East. 44 Numerous studies have also indicated a positive relationship between the articulation of a strong Christian faith and recruitment patterns within all branches of the United States military. burdette et al, for instance, find this to be true of a large cross-section of male college students; both for those they classify as 'highly religious evangelical' and 'moderately religious nonevangelical', with the 'nonreligious consistently exhibit[ing] lower odds of enlistment' overall.…”
Section: Us Versus Themmentioning
confidence: 99%